Lithium cobalt oxide positive electrode material with stable active crystal face
By adding metal ions such as Mg, Al, Ti, etc. to the ion exchange method, the active crystal surface of the lithium-ion battery positive electrode material is stabilized, and the active crystal surface of the lithium-ion battery positive electrode material is solved. The unstable and along the active crystal surface of the lithium-ion battery positive electrode material during circulation is solved. The problem of layer cracking improves the cycle life and rate performance of the battery.
Patent Information
- Application Number
- CN202411125611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-08-16
AI Technical Summary
The active crystal surface of the existing lithium-ion battery positive electrode material is unstable during the battery charging and discharging cycle, and is prone to cracking along the layer, affecting the service life.
The O3 type lithium cobalt oxide positive electrode material is prepared by ion exchange method, and a molten salt reaction additive containing M (such as Mg, Al, Ti) is added to the ion exchange reaction, and the active crystal surface is stabilized by doping and coating, especially ( 1 0 0) The crystal plane forms a spinel structure to inhibit cracking along the layer.
It significantly improves the cycle life and rate performance of the cathode material, avoids cracking along the layer, is suitable for industrial production, and is beneficial for cost and quality control.
Smart Images

Figure CN119324222A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion battery materials and electrochemistry, and in particular to a lithium ion battery positive electrode material with a stable active crystal face, a preparation method thereof and a battery. Background Art
[0002] Lithium-ion battery is a widely used secondary battery with high operating voltage, high specific capacity and high energy density. Its positive electrode active material has attracted much attention because it accounts for a large proportion of the overall cost of the battery and largely determines the theoretical energy density of the battery. The main positive electrode materials are olivine-type lithium iron phosphate LiFePO4, layered positive electrode lithium cobalt oxide LiCoO2, high nickel positive electrode LiNi x Co y Mn 1-x-y O2, lithium-rich manganese-based cathode Li[Li x Mn y Co z Ni 1-x-y-z ]O2, etc.
[0003] Ion exchange is a method of preparing positive electrode materials for lithium batteries by replacing sodium or potassium ions in the precursor with lithium ions. This method has attracted attention because it can prepare materials with thermodynamically metastable structures that cannot be prepared by general solid-phase methods. However, the positive electrode materials obtained by ion exchange will retain special active crystal faces from the precursor. The active crystal faces refer to the outer surfaces through which lithium ions are inserted and removed when the positive electrode material is working. Such crystal faces are not stable enough during the battery charge and discharge cycle. At the same time, the materials prepared by this method are prone to cracking along the layers, which is not conducive to the service life of the positive electrode materials. Summary of the invention
[0004] Based on the above problems, the present invention proposes a lithium cobalt oxide positive electrode material with a stable active crystal face, a preparation method thereof and a corresponding battery.
[0005] The present invention adopts the following technical solutions:
[0006] A lithium cobalt oxide positive electrode material with a stable active crystal surface, which is a layered O3 type lithium cobalt oxide, and its chemical formula is Li a M bCoO2, wherein M contains at least one of Mg, Al, and Ti, 0.7≤a≤1, 0.001≤b≤0.005. It is prepared by an ion exchange method, and the doping and coating of M are achieved by adding a molten salt reaction additive containing M in the ion exchange reaction. According to electron microscopy observation, the exposed active crystal plane is mainly the (1 0 0) crystal plane, and there is a gradient doping and coating effect of M ions at the exposed active crystal plane, and the doped metal ion M mainly occupies the Li layer, with a penetration depth of about 3nm. X-ray diffraction (XRD) results show the presence of the (3 1 1) peak of the Fd-3m space group, indicating that the coating layer is a spinel structure. In addition, the positive electrode material has no obvious cracking along the layer.
[0007] The method for preparing the lithium cobalt oxide positive electrode material having a stable active crystal surface of the present invention comprises the following steps:
[0008] S1. Mixing a sodium source and a cobalt source in a preset ratio and calcining the mixture to obtain a precursor;
[0009] S2. The precursor, lithium molten salt, and molten salt reaction additive are mixed uniformly according to a preset molar ratio, calcined to a temperature exceeding the melting temperature, and then kept warm to perform an ion exchange reaction. At the same time, the molten salt reaction additive dissociates and participates in the reaction in a molten state. After the reaction is completed, the product is cooled to room temperature, washed, filtered, and dried to obtain a positive electrode material for a lithium-ion battery.
[0010] Specifically, in step S1, the sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxide and sodium peroxide; the cobalt source is selected from one or more of cobalt tetroxide, cobalt trioxide, cobaltous oxide and cobalt carbonate. The sodium source and the cobalt source are mixed in proportion, heated to 800-1000 degrees Celsius and calcined for 2-10 hours to obtain the precursor P2-type Na a CoO2, 0.7≤a≤1. The morphology of its primary particles is characterized by particles with exposed (1 0 0) crystal planes.
[0011] In step S2, the molten salt reaction additive is a compound containing magnesium, aluminum and / or titanium, including but not limited to one or more of magnesium nitrate, magnesium chloride, magnesium oxide, magnesium sulfate, magnesium hydroxide, magnesium acetate, aluminum nitrate, aluminum chloride, aluminum oxide, aluminum sulfate, aluminum hydroxide, aluminum acetate, titanium dioxide, titanyl sulfate, titanium sulfate, titanium chloride, lithium titanium phosphate, and lithium aluminum titanium phosphate.
[0012] Preferably, the molten salt reaction additive is one or more of magnesium nitrate, magnesium chloride, aluminum nitrate, lithium titanium phosphate, and lithium aluminum titanium phosphate.
[0013] In step S2, the lithium molten salt is selected from one or more of lithium nitrate, lithium chloride, lithium carbonate, and lithium hydroxide, and its amount is 2-10 times the molar amount of the precursor.
[0014] In step S2, the amount of the molten salt reaction additive is as follows: the total amount of magnesium, aluminum and titanium metals contained is 0.1%-5% by mole of the precursor.
[0015] In step S2, the melting and holding temperature is 300-650°C, the holding time is 1-6 hours, and then cooling is performed.
[0016] The lithium cobalt oxide positive electrode material with stable active crystal planes of the present invention can be used to prepare positive electrode plates, which can be combined with negative electrode plates, separators, electrolytes, etc. to form lithium-ion batteries.
[0017] The beneficial effects of the present invention are:
[0018] The present invention proposes a lithium cobalt oxide positive electrode material with a stable active crystal face and a preparation method thereof. Unlike the general ion exchange method, by adding additives to the molten salt reaction system, the stabilization reaction of the active crystal face is realized for the first time during the ion exchange reaction, and the cracking along the layer is suppressed. The method can significantly improve the cycle life and rate performance of the positive electrode material prepared by the ion exchange method without adding additional processing steps, which is beneficial to cost and quality control in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The SEM images of the precursors used in the preparation of Examples 1-2 and Comparative Examples 1-2 of the present invention are shown.
[0020] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1 of the present invention.
[0021] Figure 3 TEM image (left) and electron diffraction image (right) of the positive electrode material prepared in Example 1 of the present invention.
[0022] Figure 4 The spherical aberration electron microscope image (left) and the intensity signal energy spectrum signal integral image (right) of the positive electrode material prepared in Example 1 of the present invention.
[0023] Figure 5 This is a SEM image of the positive electrode material prepared in Example 2 of the present invention.
[0024] Figure 6 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present invention.
[0025] Figure 7 The local XRD patterns of the positive electrode materials prepared in Example 1 and Comparative Example 1 of the present invention.
[0026] Figure 8 This is a SEM image of the positive electrode material prepared in Comparative Example 2 of the present invention.
[0027] Fig. 9 This is a SEM image of the positive electrode material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0028] The present invention is further supplemented by embodiments below in conjunction with the accompanying drawings, but the scope of the present invention is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0029] Example 1. Magnesium-coated O3-type lithium cobalt oxide positive electrode material
[0030] The preparation method is: take 0.4g NaCoO2 (see Figure 1 ), 0.01 g magnesium nitrate and 2 g lithium nitrate were mixed evenly in a mortar under a dry atmosphere, and the mixture was heated to 550°C at a rate of 5°C / min in a tube furnace, kept warm for 4 hours, and then cooled to room temperature, washed three times with deionized water, filtered, and dried in a blast oven at 100°C.
[0031] The pole piece preparation and battery assembly method is as follows: the magnesium-coated O3-type lithium cobalt oxide positive electrode material prepared by the above method is mixed with Super P and PVDF (polyvinylidene fluoride) at a mass ratio of 8:1:1, and ground evenly with N-methylpyrrolidone as a solvent, and then coated on aluminum foil, and placed in a blast drying oven at 100°C for 24 hours. After taking it out, it is rolled on a roller press several times and then cut into electrode discs. This is used as the positive electrode sheet, the lithium sheet is used as the negative electrode sheet, the battery separator model is Celgard 2400, and the electrolyte is Duoduo Chemical LB-726 electrolyte. It is assembled into a CR2032 button battery in a glove box with an atmosphere of O2, H2O <0.1ppm, and tested on the Xinwei battery test system at a test temperature of 30°C.
[0032] The prepared lithium cobalt oxide cathode material has no significant cracking along the layer, and the exposed active crystal plane is mainly the (1 00) crystal plane, which can be confirmed by the 120° geometric relationship of the exposed crystal plane and electron diffraction, see Figure 2 and Figure 3 The results of spherical aberration electron microscopy show that magnesium forms a coating layer and an infiltration layer at the active crystal surface. The thickness of the infiltration layer is about 3nm, and the magnesium ions mainly occupy the Li layer. Figure 4 .
[0033] Example 2. Aluminum and titanium coated O3 type lithium cobalt oxide positive electrode material
[0034] The preparation method is as follows: 0.4g NaCoO2, 0.03g lithium aluminum titanium phosphate, and 2g lithium chloride are mixed evenly in a mortar under a dry atmosphere, the mixture is heated to 650°C at a rate of 5°C / min in a tube furnace, kept warm for 4 hours, and then cooled to room temperature, then washed three times with deionized water, filtered, and dried in a 100°C blast oven. The prepared lithium cobalt oxide positive electrode material has no significant cracking along the layer, and there is a granular coating on the surface. Figure 5 .
[0035] The electrode preparation and battery assembly methods are the same as those in Example 1.
[0036] Comparative Example 1. O3 type lithium cobalt oxide No. 1
[0037] The preparation method is the same as Example 1 except that magnesium nitrate is not added. The prepared lithium cobalt oxide material has significant cracking along the layer, which is not conducive to the cycle life of the positive electrode material. Figure 6 Compared with Comparative Example 1, the XRD of the magnesium-coated O3-type lithium cobalt oxide positive electrode material prepared in Example 1 has a (3 1 1) peak of the Fd-3m space group, which corresponds to the spinel phase caused by the gradient penetration of the coating layer and metal ions on the surface. Figure 7 .
[0038] The electrode preparation and battery assembly methods are the same as those in Example 1.
[0039] Comparative Example 2. O3 type lithium cobalt oxide No. 2
[0040] The preparation method is the same as Example 2 except that lithium aluminum titanium phosphate is not added. The prepared lithium cobalt oxide material has significant cracking along the layer, which is not conducive to the cycle life of the positive electrode material. Figure 8 .
[0041] The electrode preparation and battery assembly methods are the same as those in Example 2.
[0042] The long cycle and rate performance of the lithium cobalt oxide materials prepared in Example 2 and Comparative Example 2 are shown in Table 1. It can be seen that Example 2 having a stable active crystal face has better rate performance and cycle stability.
[0043] Table 1
[0044]
[0045] Comparative Example 3. O3 type lithium cobalt oxide No. 3
[0046] The preparation method is as follows: Li2CO3 and Co3O4 are fully mixed at a Li / Co molar ratio of 1.05:1, the mixture is heated to 650°C at a rate of 5°C / min in a tube furnace, kept warm for 6 hours, cooled to room temperature, and then the product is ground with a mortar. The morphology of the lithium cobalt oxide material prepared in Comparative Example 3 is relatively round, with few edges, and the exposed active crystal face is not the (1 0 0) face. Fig. 9 .
[0047] The electrode preparation and battery assembly methods are the same as those in Example 1.
[0048] Comparative Example 4. Solid-phase sintering coating of O3-type lithium cobalt oxide
[0049] The preparation method is as follows: comparative example 3 is mixed with a 1% molar ratio magnesium acetate alcohol solution and stirred evenly, and the alcohol is evaporated at 80° C., the precipitate is heated to 650° C. and maintained for 4 hours, then cooled to room temperature, and then the product is ground with a mortar.
[0050] The electrode preparation and battery assembly methods are the same as those in Example 1.
[0051] In the charge and discharge rate of 1C = 200mA / g and the voltage range of 3-4.6V, after one cycle of activation, the long cycle performance and rate performance of the lithium cobalt oxide materials prepared in Example 1, Comparative Example 1, Comparative Example 3, and Comparative Example 4 are shown in Table 2. It can be seen that Example 1 and Comparative Example 1 with exposed active crystal plane (1 0 0) have better rate performance than Comparative Example 4 and Comparative Example 3, respectively, and Example 1 with stabilized active crystal plane has better cycle stability than Comparative Example 4.
[0052] Table 2
[0053]
[0054] The above is only a preferred embodiment of the present invention. It should be noted that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be considered as the protection scope of the present invention.
Claims
1. A lithium-ion battery cathode material is a layered O3-type lithium cobalt oxide material with a stable active crystal surface prepared by an ion exchange method, and its general chemical formula is Li a M b CoO2, where M contains at least one of Mg, Al, and Ti, 0.7≤a≤1, 0.001≤b≤0.005; the exposed active crystal plane of the material is a (1 0 0) crystal plane, and M ion gradient doping and a coating layer exist at the exposed active crystal plane, and the doped metal ions M mainly occupy the Li layer, and the coating layer is a spinel structure.
2. The lithium-ion battery positive electrode material according to claim 1, characterized in that The positive electrode material has no obvious cracking along the layers.
3. The method for preparing the positive electrode material for a lithium ion battery according to claim 1 or 2, comprising the following steps: S1, the sodium source and the cobalt source are mixed in a preset ratio and calcined to obtain the precursor P2 type Na a CoO2; S2, the precursor P2 type Na a After CoO2, lithium molten salt and molten salt reaction additive are uniformly mixed, calcined to a temperature exceeding the melting temperature and kept warm to carry out ion exchange reaction, wherein the molten salt reaction additive is a compound containing magnesium, aluminum and / or titanium; after the reaction is completed, it is cooled to room temperature, and the product is washed, filtered and dried to obtain a layered O3-type lithium cobalt oxide material with a stable active crystal surface.
4. The preparation method according to claim 3, characterized in that: In step S1, the sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxide and sodium peroxide; the cobalt source is selected from one or more of cobalt tetroxide, cobalt trioxide, cobaltous oxide and cobalt carbonate.
5. The preparation method according to claim 3, characterized in that: In step S1, the sodium source and the cobalt source are mixed, and then the temperature is raised to 800-1000° C. for calcination.
6. The preparation method according to claim 3, characterized in that: The morphology of the primary particles of the precursor obtained in step S1 is characterized by particles with exposed (1 0 0) crystal planes.
7. The preparation method according to claim 3, characterized in that: The molten salt reaction additive described in step S2 is selected from one or more of magnesium nitrate, magnesium chloride, magnesium oxide, magnesium sulfate, magnesium hydroxide, magnesium acetate, aluminum nitrate, aluminum chloride, aluminum oxide, aluminum sulfate, aluminum hydroxide, aluminum acetate, titanium dioxide, titanyl sulfate, titanium sulfate, titanium chloride, lithium titanium phosphate, and lithium aluminum titanium phosphate.
8. The preparation method according to claim 3, characterized in that: The lithium molten salt described in step S2 is selected from one or more of lithium nitrate, lithium chloride, lithium carbonate, and lithium hydroxide, and its amount is the precursor P2 type Na a 2-10 times the molar amount of CoO2.
9. The preparation method according to claim 3, characterized in that: The melting and heat preservation temperature in step S2 is 300-650°C.
10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet comprises the lithium-ion battery positive electrode material according to claim 1 or 2.
Citation Information
Patent Citations
Layered high-nickel ternary lithium ion battery positive electrode material, preparation method and application
CN115050935A
Positive plate and battery
CN116190560A
Cobalt acid lithium battery material adulterated alkaline-earth metal between layers and its preparing method
CN1763997A
Cathode material precursor and preparation method and application thereof
US20230373814A1
T2-type lithium cobalt oxide positive electrode material with space group of cmca and preparation method therefor
WO2023245880A1
Cited By
Lithium cobalt oxide composite material, preparation method, positive plate and lithium ion battery
CN121149182A